Forms of employment of people with disabilities - some aspects - Warchoł, Martyna (Journal of Education, Health and Sport, 2017)
Vocational rehabilitation of disabled persons aims to prepare and help in finding work. Thanks to her,people with disabilities can meet professionally, which raises their self-esteem. Poland offers thepossibility of employment in a protected labor market. Thanks to the disabled person learns things ofeveryday life and professional skills. Preparing her to take up work in the open labour market. There isalso the possibility of self-employment of the disabled person. This is where the person is resident in theregion with a low employment rate of people with disabilities.